Treatment with intralesional methotrexate injection in a patient with nail psoriasis - Yesim Akpinar Kara (Our Dermatology Online, 2022)
Psoriasis vulgaris is an inflammatory skin disease involving the skin, nails, and joints. While nail involvement is observed in 70-80% of patients with psoriasis, the rate of patients with isolated nail involvement is 5-10%. Dystrophies arising in the nails in psoriasis affect the patient's quality of life, and local and systemic therapies may be used as treatment. Intralesional methotrexate or corticosteroid injection might be an option in the treatment of patients with the involvement of one nail or some nails or without the involvement of the skin and joints, due to the side effects of systemic and biological agents. Herein, we report a female patient with nail psoriasis resistant to a previously applied topical treatment, the efficacy of intralesional methotrexate without the use of a systemic antipsoriatic agent, and no progression of side effects.